Experimental Investigation of the Dietary Ecology of the Extinct Passenger Pigeon, Ectopistes migratorius - Novak, Ben J.; Estes, James A.; Shaw, Holland E.; Novak, Erika V.; Shapiro, Beth (Frontiers in Ecology and Evolution, 2018)
For tens of thousands of years, passenger pigeons (Ectopistes migratorius) were a dominant member of eastern North American forest communities, with megaflocks comprising up to several billion individuals. The extinction of passenger pigeons in the early 20th century undoubtedly influenced associated species and ecosystems as interactions stemming from the pigeons disappeared suddenly. Here, we strive to better understand what was probably one of the most significant of these interactions – that between passenger pigeons and seed bearing trees. Using the band-tailed pigeon (Patagioenas fasciata) and the rock dove (Columba livia) as physical and ecological proxies, we evaluated passenger pigeon dietary range and potential to disperse seeds. Our findings suggest that the passenger pigeon’s dietary range, observed historically to be taxonomically broad, was constrained to certain seed sizes due to bill gape size. In addition, we conclude that the digestive process invariably destroyed consumed seeds but the potential for a nutrition/dispersal mutualism might still have existed via regurgitation and post-mortem release of crop contents. Our results highlight the range of ecological interactions that can be lost with species’ extinction and the inherent challenge of understanding the consequences of those interactions.